Does sinus rhythm conversion after cardiac surgery affect postoperative health- related quality of life?. Issue 1 (December 2016) - van Breugel, Henrica; Parise, Orlando; Nieman, Fred; Accord, Ryan; Lucà, Fabiana; Lozekoot, Pieter; Kumar, Narendra; van Mastrigt, Ghislaine; Nijs, Jan; Vrakking, Ries; Maessen, Jos; La Meir, Mark; et al.
Abstract Background We investigated the impact and the predictive value of sinus rhythm at 12 months (SR12 ) on subscales of three different HrQoL questionnaires: SF-36., EuroQoL and MFI 20. Methods Data of 125 cardiac surgery patients with pre-operative AF from our previous randomized trial were used. Based on their rhythm outcome patients were divided in two groups: SR12 or AF at 12 months follow up (non-SR12 ). All questionnaires were self-administered pre-operatively and at 3 months, 6 months and 12 months after surgery. Results Synus rhytm at 12 months was predictive of improvement of SF36- mental score (MS, p = 0.021), Euro-QoL-MS (p = 0.009), VAS (p = 0.006), and MFI 20-MS (p = 0.009). We failed to find any significant interactions between SR12 and any of the other significant risk factors: age <65 years, paroxysmal type of AF and preoperative AF duration <12 months. In contrast, SR12 was not significant in predicting physical score (PS) subscales of any of the questionnaires (all, p > 0.05) which were predicted by age <65 years (SF36-PS, p = 0.029) by paroxysmal type of AF and age <65 years (Euro-QoL-PS, p = 0.017 andp = 0.04, respectively) and by AF duration <12 months, paroxysmal type of AF and age < 65 years (MFI 20-PS, p = 0.019, p = 0.020 andp = 0.015, respectively). Conclusions Specific mental-related HrQoL scales are much more sensitive to sinus rhythm conversion. Sinus rithm mantainance shows significant effects on mental scores independently of other cofactors. Successful conversion to sinus rhythm after surgical ablation during cardiac surgery does not significantly affect phisical health related quality of life during 1 year follow up.